Living in Companian with Other Animals as a Feminist Way of Life: A Conversation - Cigerdelen, Dilek; Bektaş Ata, Leyla; Cosar, Simten (Feminist Asylum: A Journal of Critical Interventions, 2024)
Bektaş Ata and Coşar, members of the Feminist Asylum Editorial Collective, talk with Dilek Ciğerdelen about animal rights, veganism, feminism, and activism.